Earnings Informativeness and Strategic Disclosure: An Empirical Examination of “Pro Forma” Earnings - Lougee, Barbara A.; Marquardt, Carol A. (The Accounting Review, 2004)
This paper provides evidence on the characteristics of firms that include “pro forma” earnings information in their press releases, whether the usefulness of pro forma earnings to investors varies systematically with these characteristics, and whether the investor response to pro forma earnings is consistent with market efficiency or mispricing. Using a sample of 249 press releases from 1997–99, we find that firms with low GAAP earnings informativeness are more likely to disclose pro forma earnings than other firms. We also find that strategic considerations, measured using the direction of GAAP earnings surprises, are an important determinant of pro forma reporting. In addition, our examination of the relative and incremental information content of pro forma earnings shows that investors find pro forma earnings to be more useful when GAAP earnings informativeness is low or when strategic considerations are absent. Tests of the predictive ability of pro forma earnings for future profitability and returns are mixed, and we therefore cannot conclusively determine whether the investor reaction to pro forma earnings at the time of the press release is consistent with market efficiency or mispricing. The paper contributes to the growing literature on pro forma earnings and more generally to the literature on voluntary and strategic disclosure.